Identificando a depressão precocemente na adolescência : um estudo de neuroimagem estrutural - Cunegatto, Fernanda Rohrsetzer (2022)
Introduction: Major depressive disorder (MDD) is highly prevalent in adolescence and one of the main causes of burden and disability in this age group. In addition, there are numerous factors that establish a cause for MDD and, in the same way, there are multiple paths of predisposition to the development of the disorder. Thus, identifying brain characteristics associated with the risk and early occurrence of MDD represents important opportunities to understand the mechanisms associated with the onset of depression. Therefore, based on a composite risk score to estimate the individual probability of developing major depression among Brazilian adolescents (IDEA-RS), we included 150 Brazilian adolescents between 14-16 years of age in the Risk Stratified Cohort for the Identification of Early Depression of Adolescence (IDEARiSCo), a well-characterized sample of low-risk (LR) and high-risk (HR) for depression and with current depression (MDD). Objectives: To explore regional morphometric brain differences associated with the risk and presence of depression in adolescence through an approach based on vertices and on the structural organization of covariance networks. Methods: Cross-sectional structural neuroimaging data from the IDEA-RiSCo sample associated with the risk and presence of depression were analyzed using a vertex-based approach with measurements of cortical volume, surface area and thickness. Differences between groups in subcortical volumes were examined and differences in the organization of structural covariance networks between groups were explored. Results: From August 2018 to December 2019, 150 participants (50% female) underwent MRI scans: of these, 50 were in the LR group, 50 in the HR group and 50 in the MDD group. The mean age was 15.6 years and there were no significant differences in the proportion of adolescents who self-identified as white in the three groups. At this time, no significant differences were observed between the groups in any of the above comparisons. Considering that the analyzed data are cross-sectional, it is expected the absence of significant morphometric differences associated with the risk and presence of depression in adolescence, as reported in previous studies. Conclusion: The present study aimed to present crosssectional results of structural neuroimaging data from Brazilian adolescents with high or low risk of depression or experiencing a depressive episode. At this time, we found no significant differences in brain structure between risk/MDD groups. The follow-up of this project will certainly add more information about the development of the brain structure and possible changes related to the risk and presence of depression in adolescence.